Genetic and clinical analysis of TP73 gene in amyotrophic lateral sclerosis patients from Chinese mainland - Tang, Xuxiong; Yuan, Yanchun; Liu, Zhen; Bu, Yue; Tang, Linxin; Zhao, Qianqian; Jiao, Bin; Guo, Jifeng; Shen, Lu; Jiang, Hong; Tang, Beisha; Wang, Junling (Frontiers in Aging Neuroscience, 2023)
TP73 was recently identified as a novel causative gene for amyotrophic lateral sclerosis (ALS). However, the contribution of variations in TP73 in Chinese ALS population and other countries has yet to be reported. We screened rare, putative pathogenic TP73 mutations in a large Chinese ALS cohort and performed association analysis of both rare and common TP73 variations between cases and controls. Of the 985 ALS patients studied, six rare, heterozygous putative pathogenic variants in TP73 were identified among six unrelated sALS patients. Exon 14 of TP73 might be a mutant hotspot in our cohort. Patients with ALS with only TP73 mutations exhibited a characteristic clinical profile. Patients harboring multiple mutations in TP73 and other ALS-related genes displayed a significantly earlier onset of ALS. Our study first demonstrates that TP73 variations also have contributed to ALS in the Asian population and broaden the genotypic and phenotypic spectrum of TP73 variants in the ALS-frontotemporal dementia (FTD) spectrum. Furthermore, our findings suggest that TP73 is not only a causative gene, but may also exerts a disease-modifying effect. These results may contribute to a better understanding of the molecular mechanism of ALS.